Consumers’ willingness to consume cassava leaves as a leafy vegetable in the Kumasi Metropolis, Ghana - Fred Nimoh; Godfred O. Asare; Ismael Twumasi; Richmond Anaman (International Journal of Food Studies)
This study employs the logit model to assess the determinants of consumers’ willingness to consume cassava leaves as a leafy vegetable in the Kumasi Metropolis of Ghana. A multistage sampling technique was used to select 180 respondents for the study. The study found that majority (76%) of the respondents had no knowledge of the nutritional value of cassava leaves, though they had consumed the product before. The empirical results showed that socioeconomic characteristics of respondents such as age, sex, household size and monthly income, as well as their perceptions on the attributes and use of cassava leaves as food have significant influence on willingness to consume cassava leaves as a leafy vegetable. There is the need to provide information on the nutritional benefits of cassava leaves to facilitate decision-making on its utilisation/consumption. Programmes aimed at promoting the consumption of cassava leaves should consider the significant variables that have influence on the consumption of the product.